The bat fauna (Mammalia: Chiroptera) of Carlos Botelho State Park, Atlantic Forest of Southeastern Brazil, including new distribution records for the state of São Paulo - Vinícius Cardoso Cláudio; Gedimar Pereira Barbosa; Fabrício Braga Rassy; Vlamir José Rocha; Ricardo Moratelli (Zoologia (Curitiba), 2020)
Carlos Botelho State Park (PECB) is a large remnant of Atlantic Forest in Southeastern Brazil, with more than 37,000 ha. As its bat fauna is still unknown, we performed the first bat survey on PECB, to provide data on the distribution, natural history and taxonomy of the species. Fieldwork was conducted monthly, from October 2016 to September 2017. Captures were made using ground-level mist-nets (39600 m2.h), canopy mist-nets (2017.5 m2.h) and searches for roosts (42 hours).We captured 412 bats from 34 species of Phyllostomidae, Molossidae and Vespertilionidae. A total of 11 species were captured only in ground-level mist-nets, five in canopy mist-nets, and seven in roosts. Dermanura cinerea Gervais, 1856, Eptesicus taddeii Miranda, Bernardi & Passos, 2006, Glyphonycteris sylvestris Thomas, 1896 and Lampronycteris brachyotis (Dobson, 1879) are rare on surveys conducted in the Atlantic Forest of São Paulo and were captured in canopy mist-nets. Micronycteris schmidtorum Sanborn, 1935 and Molossus currentium Thomas, 1901 constitute the first record for the state of São Paulo, and were captured in canopy mist-nets and roosts, respectively. The species richness registered for PECB surpasses other surveys conducted in Atlantic Forest localities that use only ground-level mist-nets. Our results reinforce the importance of employing mixed capture methods, such as elevated mist-nets and searches for roosts.